Perspectives on the social, physical, and emotional impact of living with Perthes’ Disease in children and their family: a mixed methods study - Giuseppe Leo, D; Murphy, R; Gambling, T; Long, A; Jones, H; Perry, D (SAGE Publications, 2019)
Aim: To determine the social, physical, and emotional impact of living with Perthes’ disease on affected children and their family (caregivers). Patients and Methods: Through a mixed methods approach, we interviewed 18 parents and explored the perspectives of 12 children affected by Perthes’ disease (mean = 7.1 years, SD = ±4.1 years) using a survey tool. Thematic analysis of parents’ interviews provided an insight into disease-specific factors influencing patients and family’s daily life activities. Using the childhood survey tool, good and bad day scores were analyzed using MANOVA (multivariate analysis of variance). Results: Thematic analysis of the parent interviews (main themes n = 4) identified a marked effect of the disease on many facets of the child’s life, particularly pain and the impact on sleep, play, and school attendance. In addition, the interviews identified a negative effect on the family life of the parents and siblings. Children indicated that activities of daily living were affected even during “good days” (P < .05), but pain was the key limiting factor. Conclusion. Perthes’ disease negatively affects the social, physical, and emotional well-being of children and their family. These findings provide outcome domains that are important to measure in day-to-day care and add in-depth insight into the challenges caused by this disease for health care professionals involved in clinical management.